Integrated Capacity and Production Planning in The Garment Supply Chain - Endang Pudji Widjajati; Mega Cattleya PA Islami; Handy Natan Permana (Nusantara Science and Technology Proceedings, 2023)
Forecasting is the prediction, projection, or estimation of the occurrence of an uncertain event or activity in the future. The purpose of forecasting is to use the best information currently available to guide future activities to achieve the goals of the organization many strategies need to be considered and carried out by a company to make the right planning to meet the existing target demand. In a business context, forecasting is very important because it helps companies plan production, manage inventory, plan finances, and make other strategic decisions. One of the shirt production companies in Surabaya is experiencing problems in meeting production demand. This happens because the forecasting calculation of the amount of demand is not accurate so the company cannot meet consumer demand which sometimes jumps high. Based on these problems, improvements are needed by analyzing production capacity planning so the purpose of this study is to obtain accurate capacity planning using the Rough-Cut Capacity Planning (RCCP) method. Based on data processing, it can be concluded that Overtime issued a total of IDR 426.796.700, and sub-contract issued a total of IDR 117.345.600. Based on the analysis using the Rough-Cut Capacity Planning (RCCP) method, this is due to several possibilities, including the lack of accuracy when doing the forecast with the existing reality, the existence of tools and machines that experience interference (error), and other factors.